Mechanical properties of 6 finger‐trap suture techniques*. Issue 6 (8th April 2017) - Earley, Naomi F.; Meakin, Lee B.; Parsons, Kevin J.; Tarlton, John; Hall, Jon L.
Abstract: Objective: To identify the most common methods used by surgeons to place finger‐trap sutures (FTS), and determine their influence on the biomechanical properties of constructs. Study design: Questionnaire and experimental study. Methods: Six commonly used FTS methods (A‐F) were identified from literature review and questionnaire. Constructs made with 3‐metric nylon suture and 18‐French polyurethane esophagostomy tubing were tested in axial loading to failure. Two patterns (B and D) selected based on common use and biomechanical performance were further tested, with 2, 4, and 8 repeats along the tube. Displacement, load, and energy at failure were compared between constructs, and failure mode was video recorded. Results: Patterns E and F were susceptible to slipping ( P  < .001). Patterns A and D were stiffer than pattern E, and patterns A‐D were stiffer than pattern F ( P  = .012). Patterns A and B had less extension than pattern E and F, and patterns A‐D had less extension than pattern F ( P  = .002). 87.5% of FTS failed by breaking at the first suture knot. The number of repeats had no effect on FTS performance, but catastrophic failure occurred in 2 constructs with 2 repeats. Conclusion: The mechanical behavior of suture‐tube constructs and failure mode is affected by the FTS pattern. Patterns E and F are not advocated due to suture slippage. The number of repeats may not affect the FTS performance, but a minimum of 4 repeats is recommended. Overall, patterns B, C, and D performed the best in axial loading.